Respuesta :
Combine like terms
-x = 4 + 6 - 3x
-x = 10 - 3x
Isolate the x, add 3x to both sides
-x (+3x) = 10 - 3x (+3x)
-x + 3x = 10
Simplify. Combine like terms
-x + 3x = 10
2x = 10
Isolate the x, divide 2 from both sides
2x/2 = 10/2
x = 10/2
x = 5
x = 5, or A is your answer
hope this helps
-x = 4 + 6 - 3x
-x = 10 - 3x
Isolate the x, add 3x to both sides
-x (+3x) = 10 - 3x (+3x)
-x + 3x = 10
Simplify. Combine like terms
-x + 3x = 10
2x = 10
Isolate the x, divide 2 from both sides
2x/2 = 10/2
x = 10/2
x = 5
x = 5, or A is your answer
hope this helps
The answer is 5 because first you would add 3x to both sides and then you would have 2x on the left so your equation now would be 2x=4+6 which we can simplify to 2x=10 then you divide both sides by two and you get 5. Hope this helps!